Effect of freeze-drying process of collagen-activated platelet-rich plasma on transforming growth factor-β1 level - Kwartarini Murdiastuti; Fitri Yuniawati; Dahlia Herawati; Nunuk Purwanti; Dyah Ayu Mira Oktarina (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Periodontal tissue damage requires regenerative material to repair the damage. Platelet-rich plasma (PRP) is known as a regenerative material from blood which contains high level of growth factor that plays a role in wound healing and tissue remodeling. However PRP has a weakness, i.e. it is too watery so it is easily dissolved in the oral cavity, and should be used immediately after preparation. Therefore PRP storage method is needed to increase the benefits of PRP. The addition of collagen to PRP serves as a scaffold as well as an activator that stimulates the release of growth factors. One method of storing PRP is by freeze-drying process. The purpose of this study was to analyze the effect of freeze-drying process of collagen-activated PRP (PRP+C) on transforming growth factor-β1 (TGF-β1) levels. Transforming growth factor-β1 is a cytokine content in PRP, that plays a role in bone remodeling and is an important stimulator for osteoblast formation, causing chemotaxis, osteoblast proliferation and differentiation. In this study, PRP was produced from peripheral blood probandus. Platelet-rich plasma was then activated with collagen (PRP+C), and divided into two groups: freeze-dried PRP collagen (FD PRP+C); and non freeze-dried PRP+collagen (PRP+C). Transforming growth factor-β1 levels were measured using the ELISA method, followed by independent t-test. The TGF-B1 level of FD PRP+C group was significantly higher than PRP+C group (p<0.05). From this study it can be concluded that freeze-dried collagen-activated PRP has an effect to increase TGF-β1 level.